Human aspects of visualization second IFIP WG 13.7 workshop on human-computer interaction and visualization, HCIV (INTERACT) 2009, Uppsala, Sweden, August 24, 2009, revised selected papers - IFIP 2009 (2009 Uppsala, Sweden); Ebert, Achim; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the referred proceedings of the First IFIP WG 13.7 International Workshop on Human Aspects of Visualization, HCIV 2009, held in Uppsala, Sweden, in August 2009, as a satellite workshop of INTERACT 2009. The 11 revised full papers presented were carefully reviewed and selected from numerous submissions. These articles in this book give an overview of important issues concerning human-computer interaction and information visualization. They highlight the research required to understand what aspects of analysis match human capabilities most closely and how interactive visual support should be designed and adapted to make optimal use of human capabilities in terms of information perception and processing.
Electronic reproduction.
Keywords: Human-computer interaction -- Congresses; Computer vision -- Congresses; Electronic books